Gender Norms in Flux : Bride Kidnapping and Women’s Civic Participation in the Kyrgyz Republic - Muldoon, Ryan (World Bank, Washington, DC, 2017)
This exploratory small-scale, qualitative study examines the apparent backsliding on gender norms as evidenced in the Kyrgyz Republic by two observable behaviors: the rise of bride kidnapping and low women’s civic participation. Each a reflection of women’s agency, in both their private and public lives. Each has also been impacted by legal changes including a reservation system in national politics and a criminal ban on bride kidnapping. The study developed a social norms-oriented survey instrument to obtain a more detailed understanding of individual and community behaviors to gain a nuanced understanding of the forces that sustain harmful practices, and helps identify opportunities for intervention. A total of 180 in-depth individual interviews were conducted (equal number of men and women, stratified by age group), in addition to two sets of focus group discussions were held with community participants and key informants in seven communities in three geographic regions – Chui, Osh, and Naryn – covering a mix of urban and rural locations.